UM Education Performance Measurement Using Empowerment As Predictor Variable - Wardoyo, Cipto; Dwi Satrio, Yogi; Ma’ruf, Dudung (KnE Social Sciences, 2020)
There are two research variables in this study including the performance of the employees as a Independent variable and employee empowerment is a predictor variable. The purpose of this research is to understand the impact of employee empowerment variables affecting employee performance. The study entered into a quantitative descriptive research category using regression analysis techniques. The subject in this study was an employee of the education personnel of the Universitas Negeri Malang with 656 population, of course this amount is more than adequate to be researched. The thing behind this research is one because the Universitas Negeri Malang has made fundamental changes in order to improve the management of institutions, such as remuneration for both lecturers and education personnel. These fundamental changes must necessarily be followed by an increase in the performance of employees (lecturers and education personnel). The techniques in sampling used in this study use the sample of the invite with the proportion to be obtained by 260 samples. The method of data collection is doing by interview techniques, questionnaire/questionnaire, documentation, and observation. Where the results of observations show that the mechanism of empowerment of employees is less effective in improving employee performance. Keywords: Employee empowerment, employee performance